Circulating SNORD57 rather than piR-54265 is a promising biomarker for colorectal cancer: common pitfalls in the study of somatic piRNAs in cancer - Tosar, Juan Pablo (RNA, 2021)
There is increasing interest among cancer researchers in the study of Piwi-interacting RNAs (piRNAs), a group of small RNAs important for maintaining genome stability in the germline. Aberrant expression of piRNAs in cancer could imply an involvement of these regulatory RNAs in neoplastic transformation. On top of that, it could enable early cancer diagnosis based on RNA analysis in liquid biopsies, as piRNAs are not expected to widely circulate in the bloodstream of healthy individuals. Indeed, it has recently been shown that serum piR-54265 allows for excellent discrimination between colorectal cancer patients and healthy controls. However, we have also shown that most somatic piRNAs reported to date in mammals are actually fragments of other noncoding RNAs. Herein, we show that reports positioning piR-54265 as a noninvasive biomarker for colorectal cancer were actually measuring variations in the levels of a full-length (72 nt) small nucleolar RNA in serum. This should place a cautionary note for future research in somatic and cancer-specific piRNAs. We deeply encourage this line of research but discuss proper ways to identify somatic piRNAs without the interference of erroneous entries contained in piRNA databases. We also introduce the concept of miscellaneous-piRNAs (m-piRNAs) to distinguish between canonical piRNAs and other small RNAs circumstantially associated with PIWI proteins in somatic cells.